PENGARUH HYGIENE FACTORS DAN MOTIVATING FACTORS TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Raden Feizal (Universitas Mercu Buana, 2015)
Abstract: OCB behaviors can be implemented when employees get job satisfaction while toget job satisfaction, the employee needs to be fulfilled both hygienes or motivating. The aimof research want to know the fulfillment of the needs of employees can directly influence theOCB without going through job satisfaction. A population of 184 people with a samplingtechnique using simple random technique, the sample in this research Informa store staff levelemployees with the formula Slovin MAG, so that found as many as 130 employees. Datacollection using questionnaires.Data processing using path analysis.Data processing resultsshow that the path coefficient hygiene factors on job satisfaction by 0793, job satisfaction onthe OCB for 0967, hygiene factors to OCB 0038 with significant value each less than 0.05.The significant value of motivating factors on job satisfaction for 0052, and the significanceof motivating factors to OCB at 0:06. Path coefficient value of less than 0.05 can be removedand a significance value greater than 0.05 means insignificant. The conclusion was thathygiene factors directly influence job satisfaction and job satisfaction directly influence theOCB.Keywords: hygiene factors, motivating factors, job satisfaction and OCB